Large-scale ceramic–metal joining by nano-grained Ag particles paste sintering in low-temperature pressure-less conditions. (1st April 2021) - Chen, Chuantong; Suganuma, Katsuaki
Abstract: This paper proposes a method to prepare aluminum nitride (AlN) ceramic–metal joints by nano-grained Ag flake particle sintering under low temperate pressure-free conditions. A robust shear strength larger than 25 MPa was achieved at 280 °C sintering for 3 mm × 3 mm joints. Moreover, large chip (5 mm × 5 mm, 10 mm × 10 mm) bonding confirmed that the technology was not influenced by the size and can be applied to large-scale ceramic–metal joining. Further investigation confirmed that nano-grained Ag micro flake particles were easily necked together, and the AlN/Ag interface could be tightly bound at a low temperature of 180°C. This study provides a new method for low-temperature pressure-less conditions for bonding ceramic-metal structure materials on a large-scale. Graphical abstract: Image, graphical abstract